An Accreting Dwarf Star Orbiting the S-Type Giant Star π1 Gru - El Mellah, I (EDP Sciences, 2025)
Context. At the end of their lives, low- to intermediate-mass stars reach the asymptotic giant branch (AGB), during which their photospheres expand by up to several hundred times and strong stellar winds develop. These changes lead to various interactions with celestial bodies in their close circumstellar environments, including mass- and angular-momentum transfer. Aims. We aim to characterize the properties of the inner companion of the S-type AGB star π1 Gru and to identify plausible future evolutionary scenarios for this triple system. Methods. We observed π1 Gru with the Atacama Large Millimeter/sub-millimeter Array (ALMA) and the Spectro-Polarimetric High-contrast Exoplanet REsearch (SPHERE) instrument of the Very Large Telescope (VLT), collected archival photometric data, and used the HIPPARCOS-Gaia proper motion anomaly. We derived the best orbital parameters using Bayesian inference. Results. In June-July 2019, the inner companion, π1 Gru C, was located at 37.4±2.0mas from the primary (a projected separation of 6.05±0.55 au at 161.7±11.7 pc). The best orbital solution yields a companion mass of 0.86+0.22-0.20 M (using the derived mass of the primary) and a semi-major axis of 7.050.57+0.54 au, corresponding to an orbital period of 11.0-1.5+1.7 yr. The preferred solution is an elliptical orbit with eccentricity e= 0.35-0.17+0.18, although a circular orbit cannot be fully excluded. The close companion could be either a K1VK7VF9.5V star or a white dwarf (WD). Ultraviolet and millimeter continuum photometry are consistent with the presence of an accretion disk around the close companion. The ultraviolet emission may originate from hot spots in an overall cooler disk, or from a hot disk if the companion is a WD. Conclusions. Although the close companion and the AGB star are interacting and an accretion disk is observed around the companion, the mass-accretion rate is too low to trigger a Type Ia supernova, but it could produce novæevery 900 yr. Short-wavelength, spatially resolved observations are required to further constrain the nature of the C companion. Searches for close-in companions similar to this system will improve our understanding of the physics of mass and angular momentum transfer, as well as orbital evolution during late evolutionary stages. © The Authors 2025.